The European Union's Interest in Implementing The Renewable Energy Directive II (RED II) Policy on The Issue of Discrimination Against Indonesian Palm Oil - Annisa Salsabilla; khairul Munziin; Indah Karya Ningrum; Dini Septyana Rahayu (UNIDA Gontor, 2023)
The discrimination of Indonesian palm oil imposed by the European Union through the Renewable Energy Directive II (RED II) policy provides mixed and overlapping speculation. This is evident by the E.U.'s unpublished interest in the issue of discrimination against Indonesian palm oil. The purpose of this study is to find out the hidden interests or objectives of the European Union after imposing trade barriers on Indonesian palm oil exports, which will be reviewed through the theory of neo-mercantilism and also the concept of national interest. This research uses qualitative methods in collecting data related to problems using a descriptive approach to ensure a consistent understanding of the ideas considered. Our analysis shows unprecedented public interest in the European Union regarding discrimination against Indonesian palm oil. This is an effort to protect the European Union from their domestic vegetable oils being less competitive than vegetable oils from Indonesian palm oil. The European Union imposed trade barriers to prevent Indonesian palm oil from quickly entering the European market. Keywords: palm oil discrimination, European Union, RED II